2016
DOI: 10.3892/mco.2016.1071
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian steroid cell tumor, not otherwise specified: A case report and literature review

Abstract: Abstract. Steroid cell tumors (SCT), not otherwise specified (NOS) are particularly rare ovarian sex cord-stromal tumors, which comprise <0.1% of all ovarian tumors. These tumors are uncommon in patients' prior to puberty without any typical syndromes involving hirsutism, virilization and hypertension. We here in present the case of a 5-year-old female patient who presented with sudden abdominal pain, repeated vomiting and a pelvic mass. Our patient underwent urgent exploratory laparotomy and right salpingo-oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 14 publications
0
37
0
4
Order By: Relevance
“…There are steroid cell tumors that cannot be categorized as either stromal luteomas or Leydig cell tumors. This group of tumors accounts for 60% of all ovarian steroid cell tumors [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are steroid cell tumors that cannot be categorized as either stromal luteomas or Leydig cell tumors. This group of tumors accounts for 60% of all ovarian steroid cell tumors [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…The tumors can occur at any age with a mean age of 43 years, which is younger than other steroid tumors. They rarely occur before puberty [4]. Among the patients affected with SCT-NOS, 56-77% have symptoms of androgenic changes, such as hirsutism and virilization including acne, clitoral enlargement, deep voice, and alopecia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This category of tumor accounts for only 1.3-2.3% of SCST and can occur at any age, although the mean age of occurrence is 43 years [2]. SCT-NOS in children and adolescents are extremely rare, with only about 9 cases found in a PubMed search [2][3][4][5][6][7][8][9][10][11]. In some pediatric SCT-NOS cases, the functional features of steroid hormone-secreting cells produce characteristic clinical signs of virilization and Cushing's syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we describe the case of a 4-year-old girl who presented with typical symptoms of SCT-NOS before puberty: abnormal height growth, virilization, and hirsutism. All reported pediatric cases of SCT-NOS have been benign in character; however, histopathological studies in this case revealed malignant features, resulting in the decision to administer postoperative chemotherapy [2][3][4][5][6][7][8][9][10][11]. SCT-NOS of the ovary should be considered in cases of childhood virilization.…”
Section: Introductionmentioning
confidence: 99%